Why and how the millennials participate in sustainable tourism - KIM, Si Ra (KDI School, 2021)
Sustainable tourism has gained increasing attention amid the unprecedented growth in the tourism industry in recent years. Setting awareness and perception as the two important variables that shape sustainable tourism behavior, this paper aims to examine the overall awareness and perception of sustainable tourism, focusing on the Korean millennials. The millennial generation is one of the largest groups in the travel industry and known to possess pro-sustainable tourist behavior. Yet, the literature indicates that the travel motivations could vary among the millennials according to nationalities. Therefore, this research asks why and how the Korean millennials participate in sustainable tourism. Through qualitative analysis and hermeneutic phenomenology, the findings indicate that the competitive pressures faced by the Korean millennials function as a main motivational source of sustainable tourism. In addition, self-development and meaningful experience were found to be the most critical motivational factors for the Korean millennial sustainable tourists. Based on these motivational factors, this paper seeks to reappraise current sustainable tourism policies and further provide effective promotional strategies and policies to raise awareness and increase participation which can be adopted by both the government and businesses.
Thesis(Master) -- KDI School: Master of Development Policy, 2021
Keywords: Ecotourism--Korea (South); Tourism--Environmental aspects--Korea (South)